Analysis for crime prevention using ICT. A review of the scientific literature from 2015 - 2021 - Ochante-Huamaccto, Yulihño (2022)
Crime is a social problem that after the confinement of COVID-19 has increased significantly worldwide, which is why it is important to know what technological tools can be used to prevent criminal acts. In the present work, a systemic analysis was carried out to determine the importance of how to prevent crime using new information technologies. Fifty research articles were selected between 2015 and 2021. The information was obtained from different databases such as IEEE Xplore, Redalyc, Scopus, SciELO and Medline. Keywords were used to delimit the search and be more precise in our inquiry on the web. The results obtained show specific information on how to prevent crime using new information technologies. We conclude that new information technologies help to prevent crime since several developed countries have implemented their security system effectively, while underdeveloped countries do not have adequate technologies to prevent crime.